2010
DOI: 10.2298/vsp1009755k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low level laser and interferential current in the therapy of complex regional pain syndrome by infrared thermographic camera

Abstract: By the use of the infrared thermovision we showed that in the treatment of CRPS I both physical medicine methods were effective, but the effectiveness of laser therapy was statistically significantly higher compared to that of the interferential current therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
7
0
2
Order By: Relevance
“…PBMT has analgesic, anti‐edematous and anti‐inflammatory activities, and regenerative properties [21]. The use of complementary therapies such as PBMT in the treatment of CRPS aims to reduce costs and adverse effects during treatment; however, there is a dearth of studies addressing electrophysical agents and CRPS‐I [22]. Notwithstanding this, those few studies published in the literature do not share a consensus on the methodology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBMT has analgesic, anti‐edematous and anti‐inflammatory activities, and regenerative properties [21]. The use of complementary therapies such as PBMT in the treatment of CRPS aims to reduce costs and adverse effects during treatment; however, there is a dearth of studies addressing electrophysical agents and CRPS‐I [22]. Notwithstanding this, those few studies published in the literature do not share a consensus on the methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients suffering from this disease experience high medical and social costs related to loss of productivity and associated disability [10]. Although PBMT is a commonly used method to reduce pain, edema, and improve nerve regeneration [16,22,23]. Treatment protocol for CRPS, comparing different wavelengths, has not yet been performed, which justify the relevance of this study and analyze the effects of 660 and 830 nm wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Sobre a utilização da termografia na chamada medicina da dor, há relato de sua utilidade em várias situações como: síndrome da dor complexa regional, neuralgia pós-herpética, lesão cervical, atrite inflamatória, disfunção tempero-mandibular, cefaleia e síndrome de dor miofascial. 4 Nessa revisão, foram encontradas situações semelhantes como: síndrome da dor complexa regional, 13 síndrome da dor miofascial em dois estudos, 14,17 e outras situações como: dor muscular tardia,9 distensão lombar aguda, 10 lombalgia crônica, 11 artrite reumatoide, 12 osteoartrite de joelho, 15,19 Fenômeno de Raynaud's, 16 epicondilite lateral, 18 tendinites e epicondilites. 20 Sobre os recursos utilizados nos artigos analisados, estes foram variados.…”
Section: Discussionunclassified
“…O recurso terapêutico mais usado pelos estudos foi o laser. Em 5 estudos, 13,[15][16][17]20 esta modalidade foi usada. Talvez a escolha pelo laser se deu devido ao fato de ser este um recurso que pode exercer ação positiva sobre os fibroblastos, proliferação de osteoblastos, síntese de colágenos, regeneração óssea 15 além do efeito analgésicos e revascularizador, ou seja, o laser pode causar efeitos biomodulador, bioquímicos, bioelétricos e bionergéticos 21 e tem sido estudado em várias situações nas quais a reabilitação é necessária, como por exemplo, dor e tempo de fadiga em músculos espásticos em pacientes com AVC.…”
Section: Discussionunclassified
“…58 Despite their common presence, clinical trials investigated treatment options(benzodiazepines, botulinum toxin or baclofen) are all non comparative, so their effectiveness is yet to be established. 59,60 Regarding physical modalities in treatment of CRPS, there are limited evidences of superior effect of low level laser therapy to interferential currents in decreasing temperature in extremity 61 , pain, swelling and disability compared with electrotherapy (TENS and stabile galvanization) 62 Electromagnetic field therapy has been shown ineffective for CRPS in the high quality RCT. 63 Interestingly, there are no studies on transcutaneous electrical nerve stimulation(TENS) although it is an physical modality widely used for pain control, compering effects of physical and occupational therapy for CRPS, it is shown that both have positive effect on pain reduction and improved function, with some of the studies showing a slightly better effect and cost effectiveness for physical therapy 64,65 .…”
Section: Physical Therapymentioning
confidence: 99%